Cultural and Family Influences on Children's Theory of Mind Development: A Comparison of Australian and Iranian School-Age Children. (May 2014) - Shahaeian, Ameneh; Nielsen, Mark; Peterson, Candida C.; Slaughter, Virginia
Over the past three decades, considerable research effort has been expended charting how and when children develop an understanding of others' minds. Multicultural studies allow us to determine what features of this important cognitive developmental achievement might be universal and what aspects are culturally specific. However, the body of literature in this area is slim and unsystematic. The current study therefore aimed to contrast and compare the sequence through which Western and non-Western children develop a theory of mind (ToM). One hundred sixty-four 3- to 9-year-old children from Australia and Iran were assessed using an expanded ToM Scale. Although children from both cultures had equivalent overall ToM scores, more Australian children showed an understanding of diversity of beliefs and desires whereas more Iranian children understood knowledge access and sarcasm. This study is the first to compare Western and non-Western children's ToM development with a battery of ToM Scale tasks extended to include sarcasm. The cross-cultural similarities and differences revealed allow a deeper understanding of universal and culturally specific aspects of social-cognitive development.